Методи захисту інформаційних даних користувачів в сфері Voice over IP - Черкашинов, Т. К. (ХНУРЕ, 2024)
Voice over IP telephony, which is replacing telecommunications and is becoming more common every day among companies that deal with telephone communications. Since VoIP is an Internet protocol, it has several vulnerabilities that depend on the use of data transfer protocols from VoIP service providers. He is also susceptible to many attacks (DoS, man-in-the-middle attack). The transition to VoIP has not created the opportunity for such attacks, but it may make them easier to execute. The main objective of this work will be to analyze the VoIP system and its data transmission protocols, consider potential risks for attacks and apply preventive measures to complicate or eliminate the possibility of attacks. Another important task is to ensure confidentiality for VoIP users.
Keywords: Voice over IP; захист інформаційних даних користувачів